Differential equations theory, technique, and practice - Krantz, Steven G. (Steven George) 1951- (Textbooks in mathematics, 2015)
Designed for a one- or two-semester undergraduate course, Differential Equations: Theory, Technique and Practice, Second Edition educates a new generation of mathematical scientists and engineers on differential equations. This edition continues to emphasize examples and mathematical modeling as well as promote analytical thinking to help students in future studies.